Realization of High Efficiency Green Phosphorescent Top‐emitting Organic Light‐emitting Diodes by Employing Ultrathin Non‐doped Emissive Layer. Issue 1 (June 2014) - Shi, Xindong; Wang, Jing; Liu, Jun; Huang, Saijun; Wu, Xinkai; Lu, Jiangang; Chen, Chaoping; Su, Yikai; He, Gufeng; Kim, Woo Young
Abstract Green phosphorescent top‐emitting organic light‐emitting diodes (TOLEDs) based on a single ultrathin non‐doped emissive layer (EML) are investigated for utilizing the cavity standing wave effect to enhance device performance. Furthermore, double ultrathin non‐doped EMLs separated by a bi‐layer structure is introduced to balance charges and further improve the efficiency.